Artifictional intelligence against humanity's surrender to computers - Collins, H. M. (Polity Press, 2018)
Startling successes in machine intelligence using 'deep learning' have dramatically raised the stakes in the rise of AI. However, Harry Collins argues that it is still impossible to foresee a time when machines will be sufficiently embedded in society to be independent of human input or when we cannot distinguish between humans and computers.